Delivery of heliox with a semi-closed circuit during spontaneous breathing: a comparative economic theoretical study - Kubátová, Ivana; Roubík, Karel; Muller, Martin (BMC pulmonary medicine, 2015)
BACKGROUND: Heliox is a mixture of oxygen and helium which reduces airway resistance in patients with airway obstruction. In clinical practice, patients breathing spontaneously receive heliox via an open circuit. Recently, a semi-closed circuit for heliox administration has been proposed which minimizes consumption of heliox and therefore cost of the heliox therapy; although, the semi-closed circuit is associated with additional costs. The aim of the study is to conduct an economical analysis comparing total cost of heliox therapy using an open versus a semi-closed circuit in spontaneously breathing patients with airway obstruction. METHODS: Four different systems for heliox administration were analyzed: an open circuit and three alternatives of a semi-closed circuit involving a custom made semi-closed circuit and two standard anesthesia machines. Total costs of heliox therapy were calculated for all the systems. For calculation of gas consumption, the clinical procedures limiting continuous heliox therapy including the aerosol therapy, personal hygiene and nutrition were taken into account. A sensitivity analysis was conducted for main input variables that may influence the results of the study. RESULTS: Price of gases consumed by a semi-closed system represents less than 20 % of price of gases when a standard open circuit is used. This represents a saving of approximately 540 EUR per patient. The initial cost of the custom-made semi-closed circuit recuperates after treatment of 18 patients. The corresponding number of patients is 32 when a low-cost anesthesia machine is initially acquired and rises to 69 when a highly advanced anesthesia machine is considered. CONCLUSIONS: Heliox therapy in spontaneously breathing patients using a semi-closed circuit becomes more cost-effective compared to the open circuit, currently used in clinical practice, when applied in a sufficient number of cases. The impact of finding a cheaper way of heliox administration on the clinical practice needs to be ascertained.
Keywords: Airway Obstruction; helium; ekonomické modely; Models, Economic; Oxygen; kyslík; anesteziologický okruh; Humans; Costs and Cost Analysis; Anesthesia, Closed-Circuit; lidé; obstrukce dýchacích cest; Helium; náklady a analýza nákladů